Managing sustainability-related stigmatization through neutralization techniques: The case of a public hearing on pesticide use. (1st May 2022) - Boiral, Olivier; Brotherton, Marie-Christine; Talbot, David; Guillaumie, Laurence
Abstract: The objective of this article is to analyze the neutralization techniques that organizations involved in the promotion and use of pesticides use in order to respond to the sustainability-related stigma they face. This study is based on a qualitative content analysis of 77 briefs submitted to a public hearing organized by the National Assembly of Quebec (Canada) on pesticide use, which led to 30 testimonies from stakeholders that either oppose or defend the use of pesticides. This study highlights the sustainability-related stigma faced by organizations vilified because of the environmental, health and ethical issues raised at the hearing. The results also show the impression management strategies and neutralization techniques used by these organizations to respond to the stigma. These techniques are essentially based on neutralizing the stigma (denial, claims of victimhood, defense of social justice and rural traditions) and on the exemplification of existing practices (sustainability stewardship, promotion of science and progress, fight against common enemies). The article contributes to the literature on organizational stigma and on neutralization techniques by proposing an integrative model illustrating the main strategies used by companies to defend the legitimacy of controversial activities. The practical implications of the study and avenues for future research are also discussed. Highlights: Pesticide use faces increasing sustainability-related stigmatization Criticisms of pesticide use include environmental, health and ethical issues Impression management and neutralization techniques in response to stigma Use of denial, claims of victimhood, and defense of social justice and traditions Use of sustainability stewardship, promotion of science, and fight against enemies